Interpretation The Meaning Of Kanji in Basic II, Intermediate I and II Textbooks Which Have The Root Kanji Shitagokoro - Suyanti Natalia (Universitas Nasional, 2022)
Kanji are letter comes from China which are also used as a writing system in Japanese. Kanji are read in two ways, Onyomi and Kunyomi. The basic root of Kanji character is called Bushu. Bushu consists of many types of which one of them is called Shitagokoro. Bushu Shitagokoro is a root that has (kokoro) written at the bottom of a Kanji and symbolizes nature and feelings. Based on the theory of meaning of Denotation and Connotation by Gorys Keraf and the theory of the formation of Kanji or Rikusho, this study aims to determine the interpretation of the meaning of Kanji which has the basic character of Bushu Shitagokoro. This research examines using library research in the data collection stage and descriptive methods in the data analysis stage. The results obtained in this study are 12 Kanji in the form of Keisei Moji and Kaii Moji which have the basic character of Shitagokoro which are included in Jouyou Kanji or Kanji that are used in general. Keywords : Rikusho, Kanji Root, Shitagokoro, Denotation, Connotation